Railway Reform : Toolkit for Improving Rail Sector Performance - World Bank (World Bank, Washington, DC, 2018)
This Railway Reform Toolkit aims to provide an easy-to-use resource on the rail industry and to provide an experience-based set of best practices to aid in the planning and execution of railway reforms. It s based on international experiences with railway reform under a range of railway organizational forms, state agencies, state-owned, or private enterprises. The toolkit should be particularly useful to those thinking about transitions from one organizational form to another and for those seeking to improve railway performance through investment, reorganization, or changes in government policy.